2016
DOI: 10.1186/s12943-016-0566-7
|View full text |Cite
|
Sign up to set email alerts
|

NOTCH receptors in gastric and other gastrointestinal cancers: oncogenes or tumor suppressors?

Abstract: Gastric cancer (GC) ranks the most common cancer types and is one of the leading causes of cancer-related death. Due to delayed diagnosis and high metastatic frequency, 5-year survival rate of GC is rather low. It is a complex disease resulting from the interaction between environmental factors and host genetic alterations that deregulate multiple signaling pathways. The Notch signaling pathway, a highly conserved system in the regulation of the fate in several cell types, plays a pivotal role in cell differen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
30
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(30 citation statements)
references
References 160 publications
(179 reference statements)
0
30
0
Order By: Relevance
“…The medium LD between NOTCH4 rs2071286 and HLA-II rs9461776 polymorphisms suggested that a functional sequence included in the NOTCH4 and HLA-II region, could have a role in HCV-related LPDs. A potential role of NOTCH4 in the pathogenesis of HCV-related LPDs and members of the NOTCH family in several malignancies such as leukemia, gastric breast, bladder, ovarian and colon cancer were consistent with a role of NOTCH protein alteration, in the onset of some autoimmune disorders including NHL-HCV malignancies [ 31 – 34 ]. Moreover, Arcaini and co-workers observed that NOTCH pathway somatic mutations are associated with 25% of HCV-positive diffuse large B-cells lymphoma cases [ 35 ].…”
Section: Discussionmentioning
confidence: 66%
“…The medium LD between NOTCH4 rs2071286 and HLA-II rs9461776 polymorphisms suggested that a functional sequence included in the NOTCH4 and HLA-II region, could have a role in HCV-related LPDs. A potential role of NOTCH4 in the pathogenesis of HCV-related LPDs and members of the NOTCH family in several malignancies such as leukemia, gastric breast, bladder, ovarian and colon cancer were consistent with a role of NOTCH protein alteration, in the onset of some autoimmune disorders including NHL-HCV malignancies [ 31 – 34 ]. Moreover, Arcaini and co-workers observed that NOTCH pathway somatic mutations are associated with 25% of HCV-positive diffuse large B-cells lymphoma cases [ 35 ].…”
Section: Discussionmentioning
confidence: 66%
“…In addition, ibrutinib reduced phosphorylated HER2 and AKT in breast cancer (43), while sensitivity to inhibition of BTK has been demonstrated in MYC-amplified esophageal tumor lines (44). Interestingly, aberrant NOTCH signaling activation has been implicated in many of the abovementioned solid tumors (45). Therefore, our finding of the anti-NOTCH effects of ibrutinib might open new potential avenues for expanding the clinical utility of BTK inhibitors by repurposing this drug to other NOTCH-related tumors, beside CLL.…”
Section: Discussionmentioning
confidence: 88%
“…Moreover, it has been reported that notch signaling is a conserved pathway that plays a critical role in cellular functions vital for cell survival. Notch may act as both an oncogene and a suppressor in gastric cancer [40]. Epigenetic alterations of this pathway may lead to gastric cancer progression.…”
Section: Targets Of Dnmt In Gastric Cancermentioning
confidence: 99%
“…Conversely, other investigations show that NOTCH1 can promote tumorigenesis by cyclooxygenase-2 activation [43]. It seems that the function of notch pathway components is ambiguous as they were reported either as suppressor or activator of gastric carcinoma, and their exact effect on different steps of gastric cancer pathogenesis still remains unclear [40,42,[44][45]. Iroquois homeobox 1 (IRX1) is a member of Iroquois homeobox factors family that is required for embryonic development [46].…”
Section: Targets Of Dnmt In Gastric Cancermentioning
confidence: 99%